Unidirectional water transport on a two-dimensional hydrophilic channel with anisotropic superhydrophobic barriers. Issue 35 (19th August 2021) - An, Qier; Wang, Jinshu; Zhao, Feng; Li, Peiliu; Wang, Lei
Abstract : A two-dimensional titanium dioxide-based hydrophilic channel demonstrates unidirectional water transporting properties. Abstract : Many creatures have a unique anisotropic structure and special wettability on their skins, presenting intriguing water transporting properties. Inspired by the biosphere, a two-dimensional titanium dioxide-based hydrophilic channel possessing anisotropic superhydrophobic barriers was synthesized. This channel demonstrates unidirectional water transporting properties. When water is injected into the channel, fluid tends to spread in a specific direction. An asymmetric spreading resistance is generated by the different interaction modes between the liquid and superhydrophobic barriers. The superhydrophobic barriers are designed as two main styles: line and curve. As for line barriers, the included angle between barrier and horizontal is the key parameter for the unidirectional water transporting ability whereas, for curve barriers, the radius is an important variable. The best design scheme for unidirectional water transporting properties could be found by varying the parameters of these two types of barriers in the channel. Overall, this study is expected to have a significant implication in the water transporting field.